The effect of dietary niacin deficiency on reproduction of European brown hares: An experimental study - Selimovic, Aldin; Tissier, Mathilde L.; Stalder, Gabrielle; Painer-Gigler, Johanna; Haw, Anna; Rauch, Hanna; Arnold, Walter (Frontiers in Ecology and Evolution, 2023)
Large plots of maize in agricultural landscapes are associated with reduced reproductive output of females and impaired population development of free-living populations of European brown hares (Lepus europaeus, Pallas 1778). We investigated in captive brown hares experimentally whether these effects could result from an undersupply of niacin due to a suspected maize-biased diet in such areas. We repeatedly mated adult female hares, fed ad libitum either with a niacin deficient pellet mainly consisting of maize plant parts, or with the same pellet enriched with niacin to meet physiological requirements. We measured effects of the experimental feeding on body mass of females, reproductive output, growth and survival of leverets. We found significantly higher body mass of females fed the control pellet, and faster body mass gain of their leverets until standardized weaning. We found no significant difference between niacin deficient and control diet groups in reproductive output of females and survival rates of leverets. Our results show that even a diet severely depauperate of niacin affects reproductive success of female brown hares only slightly, presumably because of sufficient conversion of tryptophan to niacin, or of additional supply of niacin by caecal microorganism.